Free-standing membrane for lithium secondary battery anode and method for manufacturing same
Patent Information
- Application Number
- CN202311662977.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-14
- Filing Date
- 2023-12-06
- Publication Date
- 2025-02-21
AI Technical Summary
Existing lithium secondary batteries have problems such as safety, service time and cost when used in electric vehicles, especially the high manufacturing costs, which has affected their wide application.
An independent film containing triblock copolymer and fluorine-based resin is used as the anode material of the lithium secondary battery, and an anode active material layer is formed through the film making process to achieve excellent mechanical properties and flexibility.
This technology can significantly reduce the manufacturing cost of lithium secondary batteries, improve the mechanical properties and flexibility of the anode, be suitable for large-scale production, and effectively reduce energy consumption during the manufacturing process.
Smart Images

Figure CN119495700A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the priority of Korean Patent Application No. 10-2023-0106487 filed in the Korean Intellectual Property Office on August 14, 2023, the contents of which are incorporated herein by reference. Technical Field
[0003] In one aspect, the present invention relates to a self-supporting film for a lithium secondary battery anode using a blend of a first binder including a triblock copolymer containing a soft block and a hard block and a second binder including a fluorine-based resin and a method for manufacturing the same. Background Art
[0004] Since they were first commercialized in the 1990s, lithium secondary batteries have been widely used in the portable electronics market and continue to receive attention as the most studied energy storage system. Due to their characteristics such as high driving voltage, high energy density, low self-discharge rate, high-speed performance and long cycle stability, lithium secondary batteries meet the conditions required to be suitable as an energy source for electric vehicles.
[0005] However, there are still three major issues with lithium secondary batteries used in electric vehicles: safety, service time, and cost. The use of solid-state batteries can solve the safety and service time issues, but the cost issue has hindered the widespread application of lithium secondary batteries, so a lot of research is being conducted to reduce the cost of lithium secondary batteries.
[0006] Reducing the energy consumption required for manufacturing or increasing the thickness of the electrode is one of the most effective ways to reduce the manufacturing cost of lithium secondary batteries. In a typical method of manufacturing an electrode, a slurry obtained by mixing an electrode active material, a polymer binder and a conductive additive in water or an organic solvent is used to cast a collector, and the resulting product is dried and pressed to form an electrode, but in this way, the energy required to make the slurry and coat the collector accounts for about 50% of the energy consumed in the entire manufacturing process, so a solvent-free dry electrode manufacturing method has been studied to reduce the manufacturing cost of lithium secondary batteries.
[0007] Despite extensive research into dry electrode manufacturing methods, the development of dry electrodes with mechanical properties and flexibility suitable for large-scale production using roller-pressing equipment, etc. has not been successful, which requires further research and development. Summary of the invention
[0008] One aspect of the present invention provides a self-supporting film for a lithium secondary battery anode and a method for manufacturing the same, wherein the self-supporting film can obtain excellent mechanical properties and flexibility.
[0009] In one aspect, a self-supporting film suitable for a lithium secondary battery anode is provided, the self-supporting film comprising: a) an anode active material; b) a conductive material; c) a first binder comprising a triblock copolymer; and d) a second binder comprising a fluorine-based resin, wherein the triblock copolymer comprises a soft block and a first hard block and a second hard block, the soft block being derived from an aliphatic or alicyclic diene monomer and presenting a rubber phase at room temperature, the first hard block and the second hard block being each connected to the two ends of the soft block, being derived from an ethylenically unsaturated monomer containing an aromatic ring, and presenting a glass phase at room temperature, the first binder being in a discontinuous columnar form, connected between any one of a) an anode active material domain or b) a conductive material domain and the other of i) an anode active material domain or ii) a conductive material domain.
[0010] On the other hand, a self-supporting film for a lithium secondary battery anode is provided, comprising an anode active material, a conductive material, a first binder comprising a triblock copolymer, and a second binder comprising a fluorine-based resin. In this case, the triblock copolymer may include a soft block and a first hard block and a second hard block, the soft block being derived from an aliphatic or alicyclic diene monomer and presenting a rubber phase at room temperature, the first hard block and the second hard block being each connected to the two ends of the soft block, being derived from an aromatic ring-containing olefinically unsaturated monomer and presenting a glass phase at room temperature, and the first binder may be in a non-continuous columnar form, connected between any one of the anode active material domain or the conductive material domain and the other of the anode active material domain or the conductive material domain. On the other hand, a method for manufacturing a self-supporting film suitable for a lithium secondary battery anode is provided, the method comprising: a) using a composition for forming a lithium secondary battery anode to form an anode active material layer by a film-making process, the composition comprising: i) an anode active material; a conductive material; a layer having an average diameter (D 50 ) a first binder of triblock copolymer particles having a size of 1 μm to 50 μm; and ii) a second binder comprising a fluorine-based resin, wherein the triblock copolymer comprises a soft block and a first hard block and a second hard block, the soft block being derived from an aliphatic or alicyclic diene monomer and presenting a rubber phase at room temperature, the first hard block and the second hard block being each connected to both ends of the soft block, being derived from an aromatic ring-containing ethylenically unsaturated monomer and presenting a glass phase at room temperature.
[0011] According to another aspect of the present invention, there is provided a method for manufacturing a self-supporting film laminate for a lithium secondary battery anode, wherein the method comprises: forming an anode active material layer by a film-making process using a composition for forming a lithium secondary battery anode, the composition comprising an anode active material, a conductive material, a first binder comprising a triblock copolymer, and a second binder comprising a fluorine-based resin. In this case, the triblock copolymer may include a soft block and a first hard block and a second hard block, the soft block being derived from an aliphatic or alicyclic diene monomer and presenting a rubber phase at room temperature, the first hard block and the second hard block being each connected to the two ends of the soft block, being derived from an aromatic ring-containing ethylenically unsaturated monomer and presenting a glass phase at room temperature, and the first binder in the composition for forming a lithium secondary battery anode may include an average diameter (D 50 ) are triblock copolymer particles with a size of 1 μm to 50 μm.
[0012] In some aspects, in the self-standing film as disclosed herein, suitably, the anode active material domains or the conductive material domains are connected with the first binder in the form of non-continuous columns to form a three-dimensional network structure.
[0013] In some aspects, in a free-standing film as disclosed herein, suitably, the second binder is in the form of fibers that bind the anode active material and the conductive material.
[0014] In some aspects, in a self-standing film as disclosed herein, suitably, the anode active material and the conductive material bonded via the second binder are connected by the first binder in the form of columns.
[0015] In some aspects, in the self-standing film as disclosed herein, suitably, the mass ratio of the first binder to the second binder is 1:3 to 0.3.
[0016] In some aspects, in the self-standing film as disclosed herein, suitably, the first binder has an average width perpendicular to the machine direction of 0.1 μm to 2 μm.
[0017] In some aspects, in the self-standing film as disclosed herein, suitably, the first and second glass transition temperatures corresponding to the first and second hard blocks are independently 50°C to 120°C, and the third glass transition temperature corresponding to the soft block is -120°C to -50°C.
[0018] In some aspects, in the free-standing film as disclosed herein, suitably, the soft block is derived from an aliphatic diene-based monomer comprising at least one selected from butadiene-based monomers, pentadiene-based monomers, and hexadiene-based monomers.
[0019] In some aspects, in the self-standing film as disclosed herein, suitably, the first hard block and the second hard block are each independently derived from an aromatic ring-containing ethylenically unsaturated monomer comprising at least one of a styrene-based monomer and an aromatic (meth)acryloyl monomer.
[0020] In one aspect, a negative electrode of a lithium secondary battery is provided, comprising the composition as described herein.
[0021] In one aspect, a lithium secondary battery is provided, comprising the negative electrode as described herein.
[0022] In one aspect, there is provided a vehicle comprising a lithium secondary battery as described herein.
[0023] The term "self-standing film or sheet" or other similar terms used herein refers to a sheet that is in a form that can be handled as an independent sheet without the aid of a substrate or carrier. Therefore, the term "self-standing" can have the same meaning as "self-supporting".
[0024] The term "all-solid-state battery" as used herein includes or refers to a rechargeable battery (including a secondary battery) including a solid electrolyte (e.g., a gel or polymer (cured)), which may include ionomers and other electrolytic components for transporting ions between the electrodes of the battery. In one aspect, the lithium secondary battery mentioned herein is an all-solid-state battery.
[0025] As referred to herein, the rubber phase or rubbery state is above the Tg (glass transition temperature) of the material, i.e., where the material can be in a more rubbery state and relatively soft and pliable. Thus, when the material described herein forms a rubbery phase at room temperature (e.g., 25° C.), the material can be above its glass transition temperature and can be in a relatively rubbery or more pliable state at room temperature (25° C.).
[0026] As referred to herein, a glassy phase or glassy state is below the Tg (glass transition temperature) of a material, and wherein the material may be in a more rigid or glass-like configuration. Thus, when a material described herein forms a glassy phase at room temperature (e.g., 25° C.), at room temperature (25° C.) the material may be below its glass transition temperature and may be in a relatively rigid or hardened state.
[0027] The term "all-solid-state battery" used herein refers to a rechargeable secondary battery comprising a solid electrolyte (e.g., a gel or polymer (cured)), which may include ionomers and other electrolyte components for transferring ions between the electrodes of the battery. In a certain aspect, the lithium secondary battery mentioned herein is an all-solid-state battery.
[0028] The term "block polymer" as referred to herein includes polymers comprising two or more chemically distinct regions or segments (referred to as "blocks"), typically linked in a linear manner, such as a polymer comprising chemically distinct units that are linked (covalently bonded) end-to-end relative to the polymeric functional groups, rather than being linked (covalently bonded) in a pendant or grafted manner. In one aspect, the block polymer may comprise (i) a first polymer block comprising at least 5, 10, 20, or 30 first repeating units; and (ii) a second polymer block comprising at least 5, 10, 20, or 30 second repeating units.
[0029] As referred to herein, the terms "soft block" and "hard block" mean that the respective polymer units or parts are different in, for example, structure and one or more properties. In some aspects, the soft block may have a lower glass transition temperature or melting temperature (e.g., below room temperature) than the hard block, and the hard block may have a higher glass transition temperature or melting temperature (e.g., above room temperature) than the application temperature of the formed block copolymer material. In some embodiments, the Tg of the hard block and the soft block may be different, for example, reaching or exceeding, for example, 3°C, 5°C, 10°C, 20°C, or 30°C.
[0030] Other aspects are disclosed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The above and other aspects, features and other advantages of the present invention will be more clearly understood through the following detailed description in conjunction with the accompanying drawings, in which:
[0032] Figure 1A is a SEM image of the self-standing film according to Example 2;
[0033] Figure 1B is a diagram showing a network structure formed in a self-standing film according to Example 2;
[0034] Figure 2A is a SEM image of a composition (mixed powder) for forming a self-supporting film before manufacturing the self-supporting film of Example 2;
[0035] Figure 2B Is manufacturing Figure 2A SEM image of SBS powder before mixing the powders shown;
[0036] Figure 3A is an image taken after evaluating the flexibility of the self-standing film of Example 2 according to Experimental Example 5;
[0037] Figure 3B is an image taken after evaluating the flexibility of the self-standing film of Comparative Example 1 according to Experimental Example 5; and
[0038] Figure 3CThis is an image taken after evaluating the flexibility of the self-standing film of Reference Example 1 according to Experimental Example 5. DETAILED DESCRIPTION
[0039] The above purpose, other purposes, features and advantages of the present invention will be easily understood by the following preferred embodiments related to the accompanying drawings. However, the present invention is not limited to the embodiments described herein and can be implemented in other forms. The embodiments described herein are provided so that the disclosed content can become complete and sufficient, and the spirit of the present invention can be fully conveyed to those skilled in the art. In all the accompanying drawings, similar elements are represented by similar reference numerals. In the accompanying drawings, for the sake of clarity of the present invention, the size of the structure is larger than the actual size. The terms "first", "second" etc. used in the specification can be used to describe various components, but the components should not be interpreted as being limited to these terms. These terms are only used to distinguish one component from another component. For example, without departing from the scope of the present invention, the first component can be referred to as the second component, and the second component can also be referred to as the first component. As used in this article, unless the context clearly indicates otherwise, the singular form "one", "one" and "the / said" are intended to also include plural forms. It should also be understood that when used in this specification, the term "comprising", "including" or "having" specifies the presence of the features, regions, values, steps, operations, elements and / or components described, but does not exclude the presence or addition of one or more other features, regions, values, steps, operations, elements, components and / or combinations thereof. It should also be understood that when an element such as a layer, film, region or sheet is referred to as being "above" another element, it can be directly above another element, or there can be intermediate elements between them. Similarly, when an element such as a layer, film, region or sheet is referred to as being "below" another element, it can be directly below another element, or there can be intermediate elements between them. Unless otherwise stated, all numbers, values and / or expressions used in this article to represent the amount of components, reaction conditions, polymer compositions and mixtures should be considered to contain approximate values of various uncertainties (especially inherently existing when obtaining these values, which will affect the measured values), and are therefore understood to be modified by the term "about" in all cases. Unless otherwise stated or apparent from the context, the term "about" as used herein is understood to be within the normal tolerance range in the art, such as within two standard deviations of the mean. "About" may be understood to be within 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.1%, 0.05%, or 0.01% of the stated value. Unless the context clearly indicates otherwise, all numerical values provided herein are modified by the term "about".
[0040] In addition, when a numerical range is disclosed in this specification, the range is continuous and includes all values from the minimum value of the range to its maximum value, unless otherwise specified. In addition, when such a range involves integer values, all integers including the minimum value to the maximum value are included unless otherwise specified. For example, the range "5 to 10" will be understood to include any sub-ranges (e.g., 6 to 10, 7 to 10, 6 to 9, 7 to 9, etc.) and individual values of 5, 6, 7, 8, 9 and 10, and will also be understood to include any value between the valid integers in the range, such as 5.5, 6.5, 7.5, 5.5 to 8.5, 6.5 to 9, etc. In addition, for example, the range "10% to 30%" will be understood to include sub-ranges (e.g., 10% to 15%, 12% to 18%, 20% to 30%, etc.) and all integers (including values of 10%, 11%, 12%, 13%, etc. up to 30%), and will also be understood to include any values between the valid integers in the stated range, e.g., 10.5%, 15.5%, 25.5%, etc.
[0041] It should be understood that the term "vehicle" or "vehicle-like" or other similar terms as used herein generally include motor vehicles, such as passenger vehicles including sport utility vehicles (SUVs), buses, trucks, various commercial vehicles, watercraft including various boats and ships, aircraft, etc., and include hybrid vehicles, electric vehicles, plug-in hybrid electric vehicles, hydrogen-powered vehicles, and other alternative fuel vehicles (e.g., fuels derived from non-petroleum energy sources). As mentioned herein, a hybrid vehicle is a vehicle with two or more power sources, such as a vehicle that has both gasoline power and electric power. In certain preferred aspects, the vehicle can be electric, including a hybrid vehicle, a plug-in hybrid vehicle, or a vehicle with electricity as the primary or sole power source.
[0042] Hereinafter, a self-standing film for a lithium secondary battery anode and a method for manufacturing the same will be described in detail so that those skilled in the art to which the present invention pertains can easily implement the present invention.
[0043] Self-supporting membrane for lithium secondary battery anode
[0044] The self-supporting film for lithium secondary battery anode of the present invention is a self-supporting anode active material layer, which includes an anode active material, a conductive material, a first binder and a second binder.
[0045] The first binder may include a triblock copolymer. In this case, the triblock copolymer may include a soft block and a first hard block and a second hard block, the soft block is derived from an aliphatic or alicyclic diene monomer and presents a rubber phase at room temperature, the first hard block and the second hard block are each connected to the two ends of the soft block, derived from an aromatic ring-containing ethylenically unsaturated monomer and presents a glass phase at room temperature, and the first binder including the triblock copolymer may be in a non-continuous columnar form, connected between any one of the anode active material domain or the conductive material domain and the other of the anode active material domain or the conductive material domain.
[0046] The soft block may include repeating units derived from an aliphatic diene monomer and / or an alicyclic diene monomer and exhibit a rubber phase at room temperature, specifically, may be derived from an aliphatic diene monomer including at least one selected from butadiene monomers, pentadiene monomers, and hexadiene monomers.
[0047] The butadiene-based monomer may include at least one selected from the group consisting of 1,2-butadiene, 1,3-butadiene, isoprene, and chloroprene.
[0048] The pentadiene-based monomer may include at least one selected from the group consisting of 1,2-pentadiene, 1,3-pentadiene, 1,4-pentadiene, 2,3-pentadiene, 2-methyl-1,3-pentadiene, 2-methyl-1,4-pentadiene, 2-methyl-2,3-pentadiene, 2-methyl-2,4-pentadiene, 3-methyl-1,3-pentadiene, 3-methyl-1,4-pentadiene, 4-methyl-1,3-pentadiene, 2-ethyl ... pentadiene, 2-ethyl-1,4-pentadiene, 2-ethyl-2,4-pentadiene, 3-ethyl-1,3-pentadiene, 3-ethyl-1,4-pentadiene, 4-ethyl-1,3-pentadiene, 1-chloro-1,3-pentadiene, 1-chloro-2,4-pentadiene, 2-chloro-1,3-pentadiene, 3-chloro-1,3-pentadiene, 3-chloro-1,4-pentadiene, and 5-chloro-1,3-pentadiene.
[0049] The hexadiene-based monomer may include at least one selected from the group consisting of 1,2-hexadiene, 1,3-hexadiene, 1,4-hexadiene, 1,5-hexadiene, 2,3-hexadiene, 2,4-hexadiene, 2,5-hexadiene, 3,5-hexadiene, 2-methyl-1,3-hexadiene, 2-methyl-1,4-hexadiene, 2-methyl-1,5-hexadiene, 2-methyl-2,3-hexadiene, 2-methyl-2,4-hexadiene, 3-methyl-1,2-hexadiene, 3-methyl-1,3-hexadiene, 3-methyl-1,4-hexadiene. Hexadiene, 3-methyl-1,5-hexadiene, 3-methyl-2,4-hexadiene, 3-methyl-2,5-hexadiene, 4-methyl-1,3-hexadiene, 4-methyl-1,4-hexadiene, 4-methyl-2,3-hexadiene, 5-methyl-1,3-hexadiene, 5-methyl-1,4-hexadiene, 2-ethyl-1,3-hexadiene, 2-ethyl-1,4-hexadiene, 3-ethyl-1,2-hexadiene, 3-ethyl-1,3-hexadiene, 3-ethyl-1,4-hexadiene and 3-ethyl-1,5-hexadiene.
[0050] The soft block can be used to provide flexibility to the triblock copolymer and improve extrusion properties and abrasion resistance.
[0051] The first hard block and the second hard block may include repeating units derived from an ethylenically unsaturated monomer containing an aromatic ring and exhibit a glass phase at room temperature. Specifically, the aromatic ring contained in the ethylenically unsaturated monomer may be a substituted or unsubstituted benzene ring or a substituted or unsubstituted naphthalene ring.
[0052] In addition, the aromatic ring may be connected to the main chain or the side chain of the repeating unit of the first hard block and the second hard block, and may be preferably connected to the side chain of the repeating unit of the first hard block and the second hard block.
[0053] The first hard block and the second hard block may each independently be derived from an aromatic ring-containing ethylenically unsaturated monomer including at least one of a styrene-based monomer and an aromatic (meth)acryloyl-based monomer.
[0054] The styrene-based monomer may include at least one selected from the group consisting of styrene, α-methylstyrene, p-methylstyrene, p-methoxystyrene, p-ethoxystyrene, tert-butoxystyrene, p-acetoxystyrene, p-chlorostyrene, p-bromostyrene, 2,4-dimethylstyrene, 3,5-dimethylstyrene, and 2,4,6-trimethylstyrene.
[0055] The aromatic (meth)acryloyl monomer may include at least one selected from the group consisting of benzyl acrylate, benzyl methacrylate, phenoxy acrylate, phenoxy methacrylate, phenyl acrylate, phenyl methacrylate, phenethyl acrylate, and phenethyl methacrylate.
[0056] The first hard block and the second hard block can be firmly bonded to the anode active material or the conductive material through the π-π interaction generated by the aromatic ring structure included in the repeating unit. In addition, the first hard block and the second hard block can provide high strength performance for the triblock copolymer including the first hard block and the second hard block.
[0057] In this case, the soft block, the first hard block and the second hard block contained in the triblock copolymer can exhibit independent properties without affecting each other, so the soft block can provide appropriate flexibility, and the first hard block and the second hard block can each provide a strong bonding strength with the anode active material or the conductive material to the self-supporting film for the anode of a lithium secondary battery.
[0058] In an embodiment, any one of the anode active material domain or the conductive material domain and the other of the anode active material domain or the conductive material domain can be connected to form a three-dimensional network structure by a first binder in the form of a discontinuous column (or line). That is, any one surface of the anode active material or the conductive material and the other surface of the anode active material or the conductive material can be connected by a binder in the form of a discontinuous column (or line) to form a composite with a three-dimensional network structure in the form of a mesh (active material or conductive material is located at the intersection, and a linear binder connects these materials).
[0059] This three-dimensional network structure can be generated by the strong π-π interaction between the first hard block and the second hard block contained in the triblock copolymer and the anode active material or the conductive material. In this case, the anode active material domain or the conductive material domain and the first binder in the form of a discontinuous column can be connected to form a three-dimensional network structure, thereby improving tensile strength.
[0060] In an embodiment, the first binder may have an average width perpendicular to the longitudinal direction of 0.1 μm to 2 μm, preferably 0.2 μm to 0.8 μm, more preferably 0.3 μm to 0.7 μm. In this case, for the first binder in columnar form included in the self-supporting film for the anode of a lithium secondary battery, the average width perpendicular to the longitudinal direction refers to: an image of the first binder particles observed using a scanning electron microscope (SEM), by measuring the width perpendicular to the longitudinal direction at both ends and the center of five randomly selected columnar first binders along the longitudinal direction, and taking the average value of these measured values.
[0061] In an embodiment, the first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively, may be 50°C to 120°C, and the third glass transition temperature corresponding to the soft block may be -120°C to -50°C. Preferably, the first glass transition temperature and the second glass transition temperature may be 80°C to 120°C, and the third glass transition temperature may be -120°C to -80°C, more preferably, the first glass transition temperature and the second glass transition temperature may be 80°C to 110°C, and the third glass transition temperature may be -110°C to -80°C. Therefore, the first hard block, the second hard block and the soft block contained in the triblock copolymer have a glass transition temperature within the above numerical range, and accordingly, the self-supporting film for the anode of a lithium secondary battery containing the first binder containing the triblock copolymer may have further improved durability and flexibility, and may further more effectively maintain the shape.
[0062] In an embodiment, the amount of the first hard block and the second hard block may be 10 wt % to 60 wt %, preferably 15 wt % to 55 wt %, and more preferably 20 wt % to 50 wt % relative to the total amount of the triblock copolymer. When the amount of the first hard block and the second hard block satisfies the above numerical range, the bonding strength may be further improved due to the strong interaction with the negative active material or the conductive material, and the triblock copolymer may have appropriate flexibility to have much better molding properties.
[0063] In an embodiment, the weight average molecular weight of each of the first hard block and the second hard block may be 9,000 g / mol to 20,000 g / mol, preferably 9,500 g / mol to 20,000 g / mol, and more preferably 10,000 g / mol to 20,000 g / mol. When the weight average molecular weight of each of the first hard block and the second hard block satisfies the above numerical range, the physical crosslinking force between the first binder and the anode active material or the conductive material can be improved to form a more stable three-dimensional network structure, and can be easily deformed when manufacturing the electrode to further improve processability.
[0064] The second binder may include a fluorine-based resin. The fluorine-based resin may be in a fiber form and may be used as a matrix that supports the anode active material and the conductive material and combines the anode active material and the conductive material together. Specifically, the anode active material and / or the conductive material may be wound and bonded by the fluorine-based resin having a fiber form, in which case the anode active material and / or the conductive material bonded and fixed by the fluorine-based resin may be partially or entirely connected by the first binder in a columnar form.
[0065] In addition, compared with the first binder in the form of a column, the fluorine-based resin in the form of fibers can have a greater average length and a smaller average width perpendicular to the longitudinal direction. Therefore, the fluorine-based resin can have significantly excellent flexibility.
[0066] The fluorine-based resin can include, for example, at least one selected from the following: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene (PVDF-TrFE), polyvinylidene fluoride-tetrafluoroethylene (PVDF-TFE), polyvinylidene fluoride-chlorotrifluoroethylene (PVDF-CTFE), and polytetrafluoroethylene (PTFE).
[0067] The type of the anode active material is not particularly limited, and various known types of anode active materials can be used. For example, the anode active material can include at least one selected from carbon-based active materials, silicon-based active materials, metal-based active materials that can be alloyed with lithium, and lithium-containing active materials.
[0068] The carbon-based active material can be, for example, graphite, hard carbon, soft carbon, or graphene. The graphite can be artificial graphite, natural graphite, a mixture of artificial graphite and natural graphite, natural graphite coated with artificial graphite, or a combination thereof.
[0069] The change in the crystal structure of the carbon-based active material during the insertion and extraction of lithium ions is very small. Therefore, it can allow continuous and repeated redox reactions at the electrode to obtain a lithium secondary battery with high capacity and longer life.
[0070] The silicon-based active material can be, for example, Si, SiO m , Si-C composite material, Si-Q alloy, or a combination thereof, where m satisfies 0 < m ≤ 2, Q can be an alkali metal, an alkaline earth metal, an element of Group 13 to Group 16, a transition metal, a rare earth element, or a combination thereof, and Q does not include Si.
[0071] The metal-based active material that can be alloyed with lithium can be, for example, B, Al, Ga, In, Ge, Sn, Pb, P, As, Sb, Bi, Mg, Ca, Zn, Cd, Pd, Ag, Au, Pt, their alloys, or their oxides.
[0072] The lithium-containing active material can be, for example, lithium-containing titanium composite oxide (LTO).
[0073] The type of the conductive material is not particularly limited, and various known types of conductive materials can be used. For example, the conductive material can include at least one selected from graphite, activated carbon, carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, and carbon fibers.
[0074] The self-supporting film for the lithium secondary battery anode is a self-supporting anode active material layer and can have the form of a thin film or a film that maintains a certain shape by itself without the support of other materials. In this case, the first binder and the second binder can be used to connect the anode active material and / or the binder in the self-supporting film of the lithium secondary battery anode to maintain the shape of the self-supporting film for the lithium secondary battery anode.
[0075] As described above, the self-supporting film for the lithium secondary battery anode includes a first binder containing a triblock copolymer and a second binder containing a fluorine-based resin, and thus can have excellent mechanical properties derived from the first and second hard blocks of the triblock copolymer and excellent flexibility derived from the fibrous fluorine-based resin.
[0076] In an embodiment, the mass ratio of the first binder to the second binder is 1:3 to 0.3, 1:3 to 0.6, 1:3 to 0.75, 1:3 to 0.9, 1:2.5 to 0.9, 1:2 to 0.9, 1:1.75 to 0.9, 1:1.5 to 0.9 or 1:1.3 to 0.9, in which case the self-supporting film for the anode of a lithium secondary battery can have excellent mechanical properties and excellent flexibility, and can also have excellent adhesion to the collector and relatively low sheet resistance.
[0077] In this case, the excellent adhesion to the collector can be attributed to the π-π interaction between the aromatic ring structure contained in the repeating unit of the first hard block and the second hard block in the first binder and the collector, and the relatively low square resistance can be attributed to the fact that the first binder having a greater polarity than the second binder helps to reduce the square resistance of the self-supporting film for the anode of a lithium secondary battery. Therefore, when the mass ratio of the first binder to the second binder satisfies the above numerical range, the excellent performance produced by each of the first binder and the second binder is maximized, presumably because when the above numerical range is satisfied, the first binder and the second binder form an optimal network structure.
[0078] Anode for lithium secondary battery
[0079] The anode for a lithium secondary battery of the present invention comprises the above-mentioned self-supporting film for an anode for a lithium secondary battery and a current collector.
[0080] The collector is not particularly limited as long as the collector has high conductivity and does not cause chemical changes in the anode. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, copper, their alloys, or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used as the collector.
[0081] As described above, the triblock copolymer contained in the first binder for the self-supporting film of the lithium secondary battery anode can have excellent adhesion to the collector through the π-π interaction generated by the aromatic ring structure contained in the repeating units of the first hard block and the second hard block, so the self-supporting film for the lithium secondary battery anode can have excellent adhesion to the collector.
[0082] In an embodiment, in the current collector, a primer layer comprising a carbon-based material may be formed on the surface of one side of a self-supporting film for a lithium secondary battery anode. The carbon-based material may include, for example, at least one selected from graphite, graphene, carbon black, superconductive carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon nanotubes, graphite fibers, and carbon fibers.
[0083] The carbon-based material contained in the primer layer can have excellent adhesion to the self-supporting film for the anode of a lithium secondary battery through the π-π interaction with the aromatic ring structure contained in the repeating unit of the first hard block and the second hard block. Therefore, when the primer layer is formed, the adhesion between the self-supporting film laminate for the anode of a lithium secondary battery and the collector can be further improved.
[0084] Lithium secondary battery
[0085] The lithium secondary battery of the present invention may include the above-mentioned anode for a lithium secondary battery, cathode for a lithium secondary battery, and an electrolyte.
[0086] The cathode for a lithium secondary battery may include at least one cathode active material selected from lithium, nickel, cobalt, manganese, iron, tin, silicon, aluminum, and mixtures thereof. For example, for a cathode for a lithium secondary battery, a material such as LiCoO 2 、LiMnO 2 、LiFeO 2 、Li(Ni 0.6 Mn 0.2 Co 0.2 ) 2 、Li(Ni 0.7 Mn 0.15 Co 0.15 ) 2 、Li(Ni 0.8 Mn 0.1 Co 0.1 ) 2 、Li(Ni 0.9 Mn 0.05 Co 0.05 ) 2 、LiNi 0.6 Co 0.2 0A 0.2 O 2 、LiNi0.7 Co 0.2 0A 0.1 O 2 、LiNi 0.8 Co 0.15 Al 0.05 O 2 、LiNi 0.85 Co 0.1 Al 0.05 O 2 、LiNi 0.88 Co 0.1 Al 0.02 O 2 、LiMn 2 O 4 and LiFePO 4 cathode active material.
[0087] The electrolyte may be a liquid electrolyte or a solid electrolyte.
[0088] When the electrolyte is a liquid electrolyte, the electrolyte may contain a lithium salt and a non-aqueous organic solvent.
[0089] The lithium salt may be used without limitation as long as the lithium salt is commonly used in electrolytes of lithium secondary batteries. For example, the lithium salt may include a lithium ion battery selected from LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiN(C 2 F 5 SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 CF 3 SO 3 Li、LiC(CF 3 SO 2 ) 3 ,LiC 4 BO 8 , LiTFSI, LiFSI and LiClO 4 at least one compound in .
[0090] The non-aqueous organic solvent may include a type of organic solvent that can be used as a non-aqueous electrolyte when manufacturing a typical lithium secondary battery. In this case, the content of the non-aqueous organic solvent may be appropriately adjusted within a generally acceptable range.
[0091] Specifically, the nonaqueous organic solvent may include typical organic solvents usable as nonaqueous organic solvents for lithium secondary batteries, such as cyclic carbonate solvents, linear carbonate solvents, ester solvents, or ketone solvents, and these solvents may be used alone or in combination of two or more.
[0092] The cyclic carbonate solvent may include at least one selected from the group consisting of ethylene carbonate (EC), vinylene carbonate (VC), fluoroethylene carbonate (FEC), propylene carbonate (PC), and butylene carbonate (BC).
[0093] The linear carbonate solvent may include at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), and ethyl propyl carbonate (EPC).
[0094] The ester solvent may include at least one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, δ-valerolactone, and ε-caprolactone.
[0095] Polymethyl vinyl ketone or the like can be used as the ketone solvent.
[0096] When the electrolyte is a liquid electrolyte, the lithium secondary battery may further include a separator.
[0097] As a separator, a commonly used porous polymer film, for example, a porous polymer film prepared from a polyolefin-based polymer (e.g., ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer) can be used alone or laminated therewith, or a typical porous non-woven fabric can be used, for example, a non-woven fabric formed of high melting point glass fiber or polyethylene terephthalate fiber, but the separator is not limited thereto. In addition, a coated separator including a ceramic component or a polymer component can be used to ensure heat resistance or mechanical strength, and a separator having a single-layer structure or a multi-layer structure can be used.
[0098] In this case, the porous separator may generally have a pore size of 0.01 μm to 50 μm, and a porosity of 5% to 95%. In addition, the porous separator may generally have a thickness of 5 μm to 300 μm.
[0099] Meanwhile, when the electrolyte is a solid electrolyte, the electrolyte may be a polymer-based solid electrolyte, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, or a mixture thereof.
[0100] The polymer solid electrolyte may include, for example, polyether-based polymers, polycarbonate-based polymers, acrylate-based polymers, polysiloxane-based polymers, phosphazene-based polymers, polyethylene derivatives, alkylene oxide derivatives (e.g., polyethylene oxide), phosphate polymers, poly-stirred lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride and derivatives thereof, polymers containing ion dissociation groups. In addition, the polymer electrolyte is a polymer resin, and may be, for example, a branched copolymer, in which an amorphous polymer such as PMMA, polycarbonate, polysiloxane and / or phosphazene is copolymerized with a PEO (polyethylene oxide) main chain as a comonomer, may include a comb-like polymer resin and a cross-linked polymer resin, and at least one of them.
[0101] The oxide-based solid electrolyte may be, for example, a LLZO-based compound, a LLTO-based compound, such as Li 3x La 2 / 3- x TiO 3 , LISICON-based compounds, such as Li 14 Zn(GeO 4 ) 4 , LATP-based compounds, such as Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 , LAGP-based compounds, such as (Li 1+x Ge 2-x Al x (PO 4 ) 3 ), and LIPON-based compounds, but are not particularly limited thereto.
[0102] The sulfide-based solid electrolyte may include at least one of the following: Li 6 PS 5 Cl, Li 2 SP 2 S 5 , Li 2 S-LiI-P 2 S 5 , Li 2 S-LiI-Li 2 OP 2 S 5 , Li 2 S-LiBr-P 2 S 5 , Li 2 S-Li 2 OP 2 S 5 , Li 2 SLi3 PO 4 -P 2 S 5 , Li 2 SP 2 S 5 -P 2 O 5 , Li 2 SP 2 S 5 -SiS 2 , Li 2 SP 2 S 5 -SnS、Li 2 SP 2 S 5 -Al 2 S 3 , Li 2 S-GeS 2 or Li 2 S-GeS 2 -ZnS, but not particularly limited thereto.
[0103] Method for producing a self-supporting film for a lithium secondary battery anode
[0104] The following will describe a method for manufacturing a self-supporting film for a lithium secondary battery anode of the present invention, and the self-supporting film for a lithium secondary battery anode and components included therein will not be described again.
[0105] The method for manufacturing a self-standing film for a lithium secondary battery anode includes forming an anode active material layer by a film-making process using a composition for forming a lithium secondary battery anode, the composition comprising an anode active material, a conductive material, a first binder, and a second binder.
[0106] The first binder in the composition for forming an anode of a lithium secondary battery may include an average diameter (D 50 ) is 1 μm to 50 μm of triblock copolymer particles. The average diameter (D 50 ) represents a diameter corresponding to 50% of the volume cumulative distribution measured using a laser diffraction / scattering particle size distribution measuring instrument.
[0107] The first binder in the composition for forming the anode of a lithium secondary battery is substantially spherical, and may be a true sphere or an almost true sphere, and may specifically have an average sphericity of 0.7 to 1.0, preferably 0.8 to 1.0, and more preferably 0.9 to 1.0. That is, before manufacturing a self-supporting film for an anode of a lithium secondary battery, particles of the first binder in the composition for forming an anode of a lithium secondary battery containing the first binder may be dispersed in the composition for forming an anode of a lithium secondary battery containing the first binder, while substantially maintaining a spherical shape.
[0108] In this case, the sphericity of the first binder in the composition for forming a lithium secondary battery anode is a value obtained by observing an image of the binder particles using a scanning electron microscope (SEM), measuring the major and minor diameters of 10 randomly selected particles, calculating the minor diameter / major diameter ratio of each particle, and determining the average value of the minor diameter / major diameter ratio, and the closer the sphericity is to 1, the more spherical the particle is.
[0109] Meanwhile, the second binder in the composition for forming an anode of a lithium secondary battery may include an average diameter (D 50 ) is 10nm to 1000nm of fluorine-based resin particles. In this case, the average diameter (D 50 ) represents a diameter corresponding to 50% of the volume cumulative distribution measured using a laser diffraction / scattering particle size distribution measuring instrument.
[0110] The second binder in the composition for forming the anode of a lithium secondary battery may not have a definite form. For example, the second binder in the composition for forming the anode may be retained in a spherical form with a relatively low average sphericity and dispersed in the composition for forming the anode of a lithium secondary battery containing the second binder, or may be present on the surface of the anode active material and / or conductive material in the composition for forming the anode of a lithium secondary battery.
[0111] In the embodiment, the film-making process of the self-supporting film for the lithium secondary battery anode can be carried out by calendering (rolling). That is, the composition for forming the lithium secondary battery anode comprising the anode active material, the conductive material, the first binder and the second binder can be passed between a pair of rollers, and pressed and rolled to form a self-supporting film for the lithium secondary battery anode.
[0112] In this case, at the beginning of the membrane making process, the first binder containing a substantially spherical triblock copolymer is in contact with the anode active material or the conductive material through a high external force (shear force, tension, etc.), and then as the external force decreases at the rear end of the membrane making process, the distance between the anode active material or the conductive material increases, so that the first binder containing the triblock copolymer in contact with the surface of the anode active material or the conductive material can be flexibly deformed while maintaining adhesion, thereby forming a non-continuous columnar or linear form.
[0113] At the same time, the second binder containing an amorphous fluorine-based resin can be fiberized by applying a high external force (shear force, tension, etc.) at the beginning of the film-making process. The second binder fiberized by external force can maintain the fiber form, and the anode active material and / or the conductive material can be effectively fixed by being entangled and bonded by the fibrous fluorine-based resin.
[0114] In an embodiment, the film-making of the self-supporting film for the anode of a lithium secondary battery can be carried out at a temperature equal to or higher than the first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively. The first hard block and the second hard block are cross-linked (connected) by a physical bond with a relatively low bonding energy, and therefore can maintain the same form and size below the glass transition temperature, but can be easily formed at a temperature higher than the glass transition temperature. Therefore, when the film-making process of the self-supporting film for the anode of a lithium secondary battery is carried out at a temperature equal to or higher than the first glass transition temperature and the second glass transition temperature, each hard block contained in the triblock copolymer is flexibly deformed while maintaining bonding with the anode active material or conductive material, so the first binder part can provide a physical cross-linking point (connection point) in the form of a linear (non-continuous columnar or linear) to form a solid three-dimensional network structure around the point.
[0115] In addition, the film-making of the self-supporting film for the anode of the lithium secondary battery can be carried out at a temperature equal to or higher than the glass transition temperature of the fluorine-based resin. In this case, when the film-making of the self-supporting film for the anode is carried out at the above temperature, sufficient flexibility of the second binder can be obtained in addition, so that the bonding between the second binder and the anode active material and / or the conductive material is effectively maintained, and the second binder can be flexibly deformed to facilitate the molding of the self-supporting film for the anode of the lithium secondary battery.
[0116] In the embodiment, in the composition for forming the anode of a lithium secondary battery, the mass ratio of the first binder to the second binder can be 1:3 to 0.3, 1:3 to 0.6, 1:3 to 0.75, 1:3 to 0.9, 1:2.5 to 0.9, 1:2 to 0.9, 1:1.75 to 0.9, 1:1.5 to 0.9, or 1:1.3 to 0.9. In this case, when the mass ratio of the first binder to the second binder satisfies the above numerical range, the self-supporting film for the anode of a lithium secondary battery formed by the composition for forming the anode of a lithium secondary battery can have excellent mechanical properties and excellent flexibility, and can also have excellent adhesion to the collector and low sheet resistance.
[0117] In an embodiment, a film-making process can be performed using a dry method. That is, the composition for forming the anode of a lithium secondary battery may be substantially free of solvent. When a film-making process is performed using a wet method, the amount of loading of the electrode increased due to the liquid slurry is limited, and in some cases a network structure between a binder and an active material / conductive material may not be formed, but, since the film-making process according to the present invention is performed using a dry method, a high electrode loading amount allowing a high energy density can be obtained, and a network structure can be more effectively formed between a binder and an active material.
[0118] Method for manufacturing anode for lithium secondary battery
[0119] Hereinafter, a method for manufacturing an anode for a lithium secondary battery according to the present invention will be described, and the anode for a lithium secondary battery and components included therein will not be repeatedly described.
[0120] The method for manufacturing an anode for a lithium secondary battery may include the method for manufacturing a self-standing film for an anode for a lithium secondary battery as described above, and disposing a current collector on the self-standing film for an anode for a lithium secondary battery.
[0121] In the embodiment, the current collector may be provided by calendaring (rolling). That is, the current collector and the self-supporting film for the anode of a lithium secondary battery may be passed between a pair of rollers and pressed and rolled to form the anode for a lithium secondary battery.
[0122] In an embodiment, the arrangement of the collector (e.g., calendering) can be performed at 80°C to 200°C, 90°C to 170°C, or 95°C to 145°C, and preferably can be performed at a temperature equal to or higher than the first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively, and equal to or higher than the glass transition temperature of the fluorine-based resin. In this case, when the arrangement of the collector is performed within the above temperature range, the adhesion between the self-supporting film and the collector can be improved.
[0123] Hereinafter, the present invention will be described in more detail by way of examples. However, these examples are provided to help understand the present invention, and the scope of the present invention is not limited to these examples in any sense.
[0124] Example 1: Preparation of a self-supporting film for a lithium secondary battery anode comprising a first binder and a second binder
[0125] In the absence of a solvent, graphite as an anode active material, carbon black as a conductive material, powdered SBS triblock copolymer (glass transition temperature of the polystyrene block: 100°C, glass transition temperature of the polybutadiene block: -100°C) as a first binder, and PTFE as a second binder were mixed in a mass ratio of 96:1:1:2.
[0126] The mixed powder was rolled into a free-standing film using a twin roll press heated to 100°C.
[0127] Examples 2 and 3: Preparation of a self-supporting film for a lithium secondary battery anode comprising a first binder and a second binder make
[0128] A self-standing film was formed in the same manner as in Example 1, except that the mass ratios of the anode active material (graphite), conductive material (carbon black), first binder (SBS triblock copolymer) and second binder (PTFE) were changed as shown in Table 1 below.
[0129] Comparative Example 1: Preparation of a self-supporting film for a lithium secondary battery anode containing a second binder
[0130] The anode active material (graphite), the conductive material (carbon black), and the second binder (PTFE) were mixed in a mass ratio of 96:1:3 without a solvent.
[0131] The mixed powder was rolled into a free-standing film using a twin roll press heated to 100°C.
[0132] Reference Example 1: Preparation of a self-supporting film for a lithium secondary battery anode containing a first binder
[0133] The anode active material (graphite), the conductive material (carbon black), and the first binder (SBS triblock copolymer) were mixed in a mass ratio of 96:1:3 without solvent.
[0134] The mixed powder was rolled into a free-standing film using a twin roll press heated to 100°C.
[0135] [Table 1]
[0136]
[0137]
[0138] Experimental Example 1: SEM image observation of the mixed powder in Example 2 and the self-standing film prepared therefrom
[0139] The SEM image of the self-supporting film for anode of Example 2 was taken, as shown in FIG. Figure 1A As shown, before manufacturing the self-supporting film for the anode of Example 2, a SEM image of a mixed powder of an anode active material (graphite), a conductive material (carbon black), a first binder (SBS triblock copolymer) and a second binder (PTFE) was taken, as shown in FIG. Figure 2A In this case, only the SBS powder was taken. Figure 2B middle.
[0140] Reference Figure 1A It can be seen that after the film making process, the columnar SBS binder forms a network structure connection between the anode active materials, between the conductive materials, or between the anode active materials and the conductive materials, and is in a columnar form with an average width perpendicular to the longitudinal direction of about 0.4 μm to 0.5 μm.
[0141] In addition, it can be seen that after the membrane making process, the PTFE has a fiber form and is bonded by winding the anode active material and / or the conductive material, and parts of the anode active material and / or the conductive material bonded and fixed by the PTFE are connected by the columnar SBS binder.
[0142] In addition, it can be seen that PTFE has a larger average length and a smaller average width perpendicular to the longitudinal direction than the SBS binder.
[0143] Figure 1B Schematically showing a columnar SBS binder connected between either one of the anode active material or the conductive material and the other of the anode active material or the conductive material in the network structure of the self-standing film for the anode manufactured according to Example 2. In this case, it can be seen that the SBS binder in the form of a discontinuous column makes point contact with the outer surface of each of the active material domains or the conductive material domains, thereby generating a structure connecting these domains.
[0144] Reference Figure 2A , it can be seen that the SBS is dispersed in the mixed powder while maintaining an almost spherical shape (average diameter (D 50 ): 8 μm, average sphericity: 0.95), PTFE is mainly present on the surface of the anode active material. In addition, Figure 2B As shown in , it can be seen that before making the above mixed powder, the SBS powder is also almost spherical.
[0145] Experimental Example 2: Evaluation of tensile strength
[0146] In order to evaluate the tensile strength of the self-supporting films of Examples 1 to 3, Comparative Example 1 and Reference Example 1, each self-supporting film was punched out to have a width of 2 cm and a height of 6 cm to prepare a sample, and the sample was stretched at a rate of 5 mm / min using a UTM device while being measured to obtain a strain-length dependence graph of stress, and the tensile strength was measured based on the graph, and the results are shown in Table 2 below.
[0147] Experimental Example 3: Evaluation of the adhesion of the current collector
[0148] A current collector (8 μm thick copper foil obtained from Nexilis) coated with a primer layer (Ketjen Black) and the self-standing films of Examples 1 to 3, Comparative Example 1 and Reference Example 1 were roll-pressed using a twin-roll press heated to 100° C. to manufacture an anode for a lithium secondary battery.
[0149] Thereafter, the current collector and the self-supporting film were subjected to a peeling test according to the standard of ASTM D1876, and the results are shown in Table 2 below.
[0150] Experimental Example 4: Evaluation of Sheet Resistance
[0151] In order to evaluate the sheet resistance of the self-supporting films of Examples 1 to 3, Comparative Example 1 and Reference Example 1, each self-supporting film was punched out to have a width of 2 cm and a height of 6 cm, and then the sheet resistance was measured using a sheet resistance meter obtained from HIOKI (measurement conditions: 50 mA, 10 A), and the results are shown in Table 2 below.
[0152] [Table 2]
[0153]
[0154] Referring to Table 2, it is observed that the self-standing films of Examples 1 to 3 have excellent tensile strength and thus have excellent mechanical properties compared to the self-standing film of Comparative Example 1.
[0155] Meanwhile, the self-standing films of Examples 1 to 3 were observed to have relatively lower sheet resistance than the self-standing film of Comparative Example 1, and the self-standing film of Example 2 was also observed to have excellent adhesion than the self-standing film of Comparative Example 1.
[0156] Experimental Example 5: Evaluation of Flexibility
[0157] In order to evaluate the flexibility of the self-supporting films of Example 2, Comparative Example 1 and Reference Example 1, cylindrical rods with an average diameter of 10 mm were wrapped with the self-supporting films of Example 2, Comparative Example 1 and Reference Example 1, and the occurrence of cracks was then evaluated with the naked eye. The results are shown in Table 3 below.
[0158] [Table 3]
[0159] Flexibility Example 2 good Comparative Example 1 good Reference Example 1 Difference
[0160] Referring to Table 3, it can be confirmed that the self-supporting films of Example 2 and Comparative Example 1 have greater flexibility than the self-supporting film of Reference Example 1.
[0161] Specifically, refer to Figure 3A , when the cylindrical rod was wrapped with the self-supporting film of Example 2, no cracks were observed in the self-supporting film of Example 2. Figure 3B Even when the cylindrical rod was wrapped with the self-supporting film of Comparative Example 1, no cracks were observed in the self-supporting film of Comparative Example 1. Figure 3C , when a cylindrical rod was wrapped with the self-standing film of Reference Example 1, cracks were observed in the self-standing film of Reference Example 1 due to lack of flexibility.
[0162] Experimental Example 6: Evaluation of tensile strength according to the width of the produced film
[0163] The tensile strength of the self-supporting films of Example 2, Comparative Example 1 and Reference Example 1 was measured when the width of the produced films was set to 100 mm, 200 mm and 300 mm, and the results are shown in Table 4 below.
[0164] In this case, the tensile stress measured in Experimental Example 2 was multiplied by the cross-sectional area of each of the self-standing films having different produced film widths to measure the tensile strength.
[0165] [Table 4]
[0166]
[0167] Referring to Table 4, like the self-supporting film of Reference Example 1, the self-supporting film of Example 2 showed excellent total tensile strength regardless of the film manufacturing width value of 100 mm, 200 mm, or 300 mm.
[0168] In contrast, the self-standing film of Comparative Example 1 showed poor tensile strength at all film manufacturing widths of 100 mm, 200 mm, and 300 mm, and it was less than the minimum tensile strength of 5N used in a commonly used rolling apparatus.
[0169] Referring to the above description, the self-supporting films of Examples 1 to 3 comprising a blend of the first binder and the second binder have greater tensile strength than the self-supporting film of Comparative Example 1 comprising only the second binder, and exhibit excellent total tensile strength regardless of the film manufacturing width value of 100 mm, 200 mm or 300 mm, and are therefore determined to have excellent mechanical properties and greater flexibility than the self-supporting film of Comparative Example 1.
[0170] From this, it can be seen that the self-standing films of Examples 1 to 3 having excellent mechanical properties and excellent flexibility are suitable for mass production using a rolling device or the like, compared with the self-standing film of Comparative Example 1.
[0171] At the same time, it was observed that the self-supporting films of Examples 1 to 3 had relatively low sheet resistances compared to the self-supporting film of Comparative Example 1, and specifically, the self-supporting films of Examples 1 and 2 had relatively low sheet resistances. In addition, it was observed that the self-supporting film of Example 2 had excellent adhesion compared to the self-supporting film of Comparative Example 1.
[0172] Therefore, it can be seen that, among the self-standing films of Examples 1 to 3 having excellent mechanical properties and excellent flexibility, the self-standing film of Example 2 is more excellent in sheet resistance and adhesion properties.
[0173] The self-supporting film for a lithium secondary battery anode of the present invention can have excellent mechanical properties derived from the triblock copolymer contained in the first binder and excellent flexibility derived from the fluorine-based resin contained in the second binder, and thus can achieve mass production using a rolling device or the like.
[0174] While the present invention has been shown and described in connection with the exemplary embodiments, it will be apparent to those skilled in the art that modifications and variations can be made without departing from the spirit and scope of the invention as defined by the appended claims.
Claims
1. A self-supporting film suitable for a lithium secondary battery anode, the self-supporting film comprising: Anode active material; Conductive materials; a first binder comprising a triblock copolymer; and a second binder comprising a fluorine-based resin, The triblock copolymer comprises a soft block and a first hard block and a second hard block, wherein the soft block is derived from an aliphatic or alicyclic diene monomer and exhibits a rubber phase at room temperature, and the first hard block and the second hard block are each connected to two ends of the soft block, derived from an aromatic ring-containing ethylenically unsaturated monomer and exhibit a glass phase at room temperature, and The first binder is in the form of discontinuous columns, connected between any one of a) the anode active material domain or b) the conductive material domain and the other of i) the anode active material domain or ii) the conductive material domain.
2. The self-supporting film suitable for lithium secondary battery anode according to claim 1, wherein: The anode active material domains or the conductive material domains are connected with a first binder in the form of discontinuous columns to form a three-dimensional network structure.
3. The self-supporting film suitable for lithium secondary battery anode according to claim 1, wherein: The second binder is in the form of fibers and binds the anode active material and the conductive material.
4. The self-supporting film suitable for lithium secondary battery anode according to claim 1, wherein: The anode active material and the conductive material bound by the second binder are connected by the first binder in the form of columns.
5. The self-supporting film suitable for lithium secondary battery anode according to claim 1, wherein: The mass ratio of the first binder to the second binder is 1:3 to 0.
3.
6. The self-supporting film suitable for lithium secondary battery anode according to claim 1, wherein: The first binder has an average width perpendicular to the longitudinal direction of 0.1 μm to 2 μm.
7. The self-supporting film suitable for lithium secondary battery anode according to claim 1, wherein: The first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively, are independently 50° C. to 120° C., and The third glass transition temperature corresponding to the soft block is -120°C to -50°C.
8. The self-supporting film suitable for lithium secondary battery anode according to claim 1, wherein: The soft block is derived from an aliphatic diene-based monomer including at least one selected from a butadiene-based monomer, a pentadiene-based monomer, and a hexadiene-based monomer.
9. The self-supporting film suitable for lithium secondary battery anode according to claim 1, wherein: The first hard block and the second hard block are each independently derived from an aromatic ring-containing ethylenically unsaturated monomer including at least one of a styrene-based monomer and an aromatic (meth)acryloyl-based monomer.
10. The self-supporting film suitable for lithium secondary battery anode according to claim 1, wherein: The fluorine-based resin includes at least one selected from the group consisting of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trifluoroethylene, polyvinylidene fluoride-tetrafluoroethylene, polyvinylidene fluoride-chlorofluoroethylene, and polytetrafluoroethylene.
11. An anode for a lithium secondary battery, the anode comprising: Current collector; and A self-supporting film suitable for lithium secondary battery anode according to claim 1.
12. The anode for a lithium secondary battery according to claim 11, wherein The current collector further includes a primer layer containing a carbon-based material on a surface on a side where the self-standing film for a lithium secondary battery anode is provided.
13. A lithium secondary battery comprising: The anode for a lithium secondary battery according to claim 11; Cathodes for lithium secondary batteries; and Electrolytes.
14. A method for manufacturing a self-supporting film suitable for a lithium secondary battery anode, the method comprising: An anode active material layer is formed by a film-making process using a composition for forming an anode of a lithium secondary battery, the composition comprising: Anode active material; Conductive material; a first binder comprising a triblock copolymer; and a second binder comprising a fluorine-based resin, wherein the copolymer particles of the triblock copolymer have an average diameter D of 1 μm to 50 μm 50 , The triblock copolymer comprises a soft block and a first hard block and a second hard block, wherein the soft block is derived from an aliphatic or alicyclic diene monomer and presents a rubber phase at room temperature, and the first hard block and the second hard block are respectively connected to the two ends of the soft block, are derived from an aromatic ring-containing ethylenically unsaturated monomer and present a glass phase at room temperature.
15. The method for producing a self-supporting film suitable for a lithium secondary battery anode according to claim 14, wherein: The mass ratio of the first binder to the second binder is 1:3 to 0.
3.
16. The method for producing a self-supporting film suitable for a lithium secondary battery anode according to claim 14, wherein: The first binder comprises spherical particles having an average sphericity of 0.8 to 1.
0.
17. The method for producing a self-supporting film suitable for a lithium secondary battery anode according to claim 14, wherein: The film forming process is performed using a dry method.
18. The method for producing a self-supporting film suitable for a lithium secondary battery anode according to claim 14, wherein: The film-making process is performed at a temperature equal to or higher than a first glass transition temperature and a second glass transition temperature corresponding to the first hard block and the second hard block, respectively.
19. A method for manufacturing an anode for a lithium secondary battery, the method comprising: a) forming the anode active material layer as claimed in claim 14; and b) placing a current collector on the formed anode active material layer.
20. A vehicle comprising the lithium secondary battery as claimed in claim 13.
Citation Information
Patent Citations
Method for preparing ginsenoside compound k composition
KR1020230106487A